2007
DOI: 10.1016/j.jde.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The central configurations of four masses x, −x, y, −y

Abstract: The configuration of a homothetic motion in the N -body problem is called a central configuration. In this paper, we prove that there are exactly three planar non-collinear central configurations for masses x, −x, y, −y with x = y (a parallelogram and two trapezoids) and two planar non-collinear central configurations for masses x, −x, x, −x (two diamonds). Except the case studied here, the only known case where the four-body central configurations with non-vanishing masses can be listed is the case with equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…While vorticities may be negative, we always assume m i O0 for all i, 1%i%n. Note that this implies lO0 (for results with some negative masses, see Celli (2007) andO'Neil (2007)). The main result we prove in this article is as follows.…”
Section: Introductionmentioning
confidence: 95%
“…While vorticities may be negative, we always assume m i O0 for all i, 1%i%n. Note that this implies lO0 (for results with some negative masses, see Celli (2007) andO'Neil (2007)). The main result we prove in this article is as follows.…”
Section: Introductionmentioning
confidence: 95%
“…Perez-Chavela and Santoprete [13] show the existence of kite central configurations for a pair of symmetric masses and show that such a configuration must always possess a symmetry. Similarly, Celli [34] proves the existence of planar diamond and trapezoidal central configurations for two pairs of equal masses. Corbera and Llibre [35] give a complete classification of the same problem and show that this setup has exactly 34 different classes of central configurations.…”
Section: Introductionmentioning
confidence: 78%
“…In this paper we assume an equation of motion for the particles different from that used in references [3], [4], [5]. We will show that their equation of motion applied to two particles of opposite charge, leads to a contradiction with Newton's first law of motion: under no external force, a body moves with a constant velocity vector.…”
Section: Appendixmentioning
confidence: 99%
“…where r j denotes the position vector of particle j in 3D-space, m j is its positive mass, G is the positive constant of universal gravitation, r lj = |r l − r j | is the distance between particles j and l, and e j is the charge of particle j such that m j = |e j |, with two possible choices of sign for the charge. In the mathematical literature we have found some papers in the context of determining Four-Body central configurations that consider negative masses [3], [4], [5], with a different equation of motion, a different definition of central configuration and without distinguishing between masses and charges. The difference with respect to the differential equation of motion used in those papers is stressed in an Appendix at the end of the paper, where, assuming the validity of Newton's second and third laws, the equation of motion used by those Authors is shown to produce, for a system of two masses of equal magnitude but different inertial and gravitational sign, a rigid body which is self-accelerated under no external force, violating Newton's first law expressing that a body subject to no external forces moves with constant velocity.…”
Section: Introductionmentioning
confidence: 99%